2011
DOI: 10.1002/eco.128
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of cellulose filters as a standardized material for measuring litter breakdown in headwater streams

Abstract: The decay rate of cellulose filters and associated chemical and biological characteristics were compared with those of white oak (Quercus alba) leaves to determine whether cellulose filters could be a suitable standardized material for assessing deciduous leaf breakdown in headwater streams. The comparison was done across reaches draining mixed deciduous forest and post-coal mining catchments, in natural and constructed channels, and ranged in flow duration from ephemeral to perennial. Decay rates of leaves an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The 'Shirley Soil Burial Test Fabric' was subsequently used in aquatic ecosystems where it was found to be sensitive to variation in environmental conditions (Hildrew et al, 1984;Boulton and Quinn, 2000;Claret et al, 2001;Tiegs et al, 2007). Unfortunately, the manufacture of Shirley material was discontinued in 2002, creating need for a new standard (Fritz et al, 2011). Several materials have since been used including 'Calico' cloth (Imberger et al, 2010), 'Artist's canvas' (Slocum et al, 2009), also known as 'Artist's fabric' (Tiegs et al, 2013) and 'Empa material' (Clapcott et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The 'Shirley Soil Burial Test Fabric' was subsequently used in aquatic ecosystems where it was found to be sensitive to variation in environmental conditions (Hildrew et al, 1984;Boulton and Quinn, 2000;Claret et al, 2001;Tiegs et al, 2007). Unfortunately, the manufacture of Shirley material was discontinued in 2002, creating need for a new standard (Fritz et al, 2011). Several materials have since been used including 'Calico' cloth (Imberger et al, 2010), 'Artist's canvas' (Slocum et al, 2009), also known as 'Artist's fabric' (Tiegs et al, 2013) and 'Empa material' (Clapcott et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While cotton cloth responded to environments of air temperature, precipitation and drawdown % in ways predicted by the literature and hypotheses tested in this study, the actual responses of wood and leaf litter decomposition to these environments was quite different than cloth (Table 2). Other studies have observed this same problem with proxy materials; cellulose filter degradation was little related to the decomposition response of Quercus alba leaves in streams [64]. These studies bring into question the validity of using proxy materials to represent plant litter responses to environment in decomposition studies, at least without careful comparisons in specific environments.…”
Section: Independent Climatic or Environmental Variablementioning
confidence: 89%
“…Understanding the impacts of surface mining on aquatic ecology, streamwater chemistry and hydrology has also been a major T A B L E 1 Summary of available streamflow and water-quality records for Robinson Forest T A B L E 3 Summary of methods and measurement uncertainties for precipitation and stream-water chemistry analyses (1971-1999; methyl orange titration method); then titration to pH endpoint (pH = 4.5; 1999-2016); subsequently, titration to colour endpoint (metyl orange method). focus of work at Robinson Forest (Agouridis et al, 2017;Burke et al, 2014;Fritz et al, 2011;Hutton et al, 2020;Mastin et al, 2012;Muncy et al, 2014;Pond et al, 2016;Price et al, 2016;Price et al, 2018;Strohm, 2014;. The network has been utilized to evaluate the effectiveness of forestry best management practices for protecting water resources (Adkins et al, 2016;Barton et al, 2017;Bowker et al, 2020;Maigret et al, 2014;Witt et al, 2013;Witt et al, 2016).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Recent projects include the characterization and modelling of hydrology in headwater streams of eastern Kentucky (Blackburn‐Lynch et al, 2017; Villines et al, 2015; Williamson et al, 2015). Understanding the impacts of surface mining on aquatic ecology, streamwater chemistry and hydrology has also been a major focus of work at Robinson Forest (Agouridis et al, 2017; Burke et al, 2014; Fritz et al, 2011; Hutton et al, 2020; Mastin et al, 2012; Muncy et al, 2014; Pond et al, 2016; Price et al, 2016; Price et al, 2018; Strohm, 2014; Williamson & Barton, 2020). The network has been utilized to evaluate the effectiveness of forestry best management practices for protecting water resources (Adkins et al, 2016; Barton et al, 2017; Bowker et al, 2020; Maigret et al, 2014; Witt et al, 2013; Witt et al, 2016).…”
Section: Site Descriptionmentioning
confidence: 99%